(untitled) (REMUNOM, 2025)
This article analyzes the socioeconomic profile of students entering the 2025.1 semester of Administration, Accounting, and Law courses at the Codó campus of the Maranhão State University (UEMA). The research arose from the need to understand the social, economic, and educational characteristics of these students, considering that, despite the advances in higher education access policies, such as the Higher Education Access Selection Process (PAES), many still face barriers that hinder their continued university studies. The data were obtained through a questionnaire administered to 79 students, covering information on gender, age, color/race, parents’ education, family income, housing, transportation, and employment status. The results indicate that most students are young, female, self-identified as mixed race, from public schools and with a family income of up to two minimum wages. In addition, a significant portion have already considered dropping out of the course due to financial or social difficulties. These data reinforce the importance of expanding student assistance policies, aiming to guarantee not only access, but also the permanence of students in higher education. The study contributes to the reflection on the reality of students from the interior of Maranhão and can help in the formulation of more inclusive and effective institutional actions.